Rehabilitation Measures for Suspected Narcotics Addicts at the Police Investigation Stage (Study at the North Sumatra Police Drug Investigation Directorate) - Wenny Moechtar; Tengku Erwinsyahbana; Alpi Sahari (International Journal Reglement & Society (IJRS), 2022)
The arrest of narcotics addicts to become suspects and so they can be rehabilitated, through several processes that are not easy. Therefore, some people must know about the process of handling it. This study aims to analyze the legal arrangements for rehabilitation actions for suspected narcotics addicts at the investigation stage in the police, the case investigation system in Narcotics Crimes at the North Sumatra Police Narcotics Investigation Directorate and the implementation of rehabilitation for suspected narcotic addicts at the examination stage at the Sumatra Regional Police Narcotics Investigation Directorate. North. This research method uses empirical research with primary data types, by conducting interviews at the Directorate of Drug Investigation of the Regional Police of North Sumatra. Based on the results of the study that the rehabilitation measures for suspected narcotics addicts were at the investigation stage in 2019 nil, 2020 nil, while in 2021 as many as 89 suspects and in 2022 as many as 4 suspects were carried out rehabilitation actions at the investigation stage at the North Sumatra Police Narcotics Directorate, as for the factors The obstacle in implementing rehabilitation measures for suspected narcotics addicts is related to the financing that must be issued by the suspect and the lack of availability of rehabilitation centers that can accept suspected narcotics addicts due to the large number of narcotics addicts